'1 Must 5 Reductions (1M5R)' integrated rice management package adopted in Vietnam - CGIAR Research Program on Rice (2021)
1M5R or ‘Mot Phai, Nam Giam’ is certified by a Presidential decree (532-QD-TT-CLT) as the national policy to promote best management practices in lowland rice cultivation.